MARKETED SURPLUS JAGUNG DAN DAMPAKNYA TERHADAP KETERSEDlAAN PANGAN NON BERAS DI PROVINSI BENGKULU - Nusril, Nusril; Andani, Apri; Nabiu, Musryadi (Jurnal AGRISEP, 2010)
In general, focus of this study is to estimate  non-rice food farmer market participation  in Bengkulu  Province  in order to provide  information  about and variety availability  of food, especially  maize. Research  sample areas are seven districts namely Mukomuko, North Bengkulu,  Seluma, South Bengkulu, Kaur, Kepahiang, and Rejang Lebong. This research used the marketable surplus analysis, and market  participation  analysis to examine the availability of maize. This research found that maize has adequate potency as a substitution food. This commodity can fulfill approximately  12 percent of requirement  for Bengkulu province resident. For Bengkulu farmers,  maize is not an alternative food for their household members, but it has significant  role for household economies. Furthermore,  the research also found  that maize production is  able to  supply energy for  every Bengkulu resident approximately  244.09 kcal/capitajday.  This equals to 11.90 % of energy  required to conduct normal or daily activities.